2014
DOI: 10.1007/s13277-014-2780-5
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of 14-3-3ζ expression in intrahepatic cholangiocarcinoma and its clinical implications

Abstract: The 14-3-3 proteins are highly conserved molecules that are involved in many vital biologic processes and are associated with the progression of cancer. The role of 14-3-3ζ, a dimeric isoform of 14-3-3, in intrahepatic cholangiocarcinoma (ICC) was investigated in this study. The expression of 14-3-3ζ in tumour samples from patients with ICC was examined by Western blot and immunohistochemistry, and the correlation between its expression and various clinicopathological features was determined. Then, the capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Neal et al also reported that an elevated level of 14-3-3ζ was associated with reduced survival and increased recurrence in breast cancer [14]. Moreover, Zhang et al reported that 14-3-3ζ overexpression indicated poor prognosis of intrahepatic cholangiocarcinoma in terms of a shorter patient survival and a higher recurrence [19]. In our previous study, we reported that 14-3-3ζ overexpression was significantly correlated with a shorter survival time and a higher recurrence rate in HCC [20].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Neal et al also reported that an elevated level of 14-3-3ζ was associated with reduced survival and increased recurrence in breast cancer [14]. Moreover, Zhang et al reported that 14-3-3ζ overexpression indicated poor prognosis of intrahepatic cholangiocarcinoma in terms of a shorter patient survival and a higher recurrence [19]. In our previous study, we reported that 14-3-3ζ overexpression was significantly correlated with a shorter survival time and a higher recurrence rate in HCC [20].…”
Section: Discussionmentioning
confidence: 97%
“…Of types of the 14-3-3 proteins, 14-3-3ζ has been found to promote anchorage-independent growth and proliferation, inhibit apoptosis, and enhance chemo-resistance and metastasis of cancer cells [11,12]. In addition, a high level of 14-3-3ζ is correlated with poor prognosis of multiple cancers, including breast cancer [13,14], non-small cell lung cancer [15][16][17], gastric carcinoma [18], intrahepatic cholangiocarcinoma [19], and HCC [20]. A previous study showed that overexpression of 14-3-3ζ could lead to the activation of Akt in human mammary epithelial cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria were described in our previous study 16. Ethical approval was obtained from Zhongshan Hospital Research Ethics Committee, and all patients signed an informed consent form.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue microarray (TMA) was constructed and immunohistochemistry (IHC) was performed as described in our previous study 16. The antibodies used for IHC are listed in online supplementary table S1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, 14-3-3zeta and aPKC-ι [121,122], adrenomedullin [123], Forkhead box protein C2 [124], WAVE3 [125] and Fibroblast growth factor (FGF)19/FGFR4 axis [126] promote EMT in CCA. Conversely, FBXW7 [127,128], thymosin β10 [129] and MAP3K4 [130] act as negative regulators of EMT through inhibition of mTOR, ERK1/2 and NFκB pathways, respectively.…”
Section: Additional Regulatory Factorsmentioning
confidence: 99%